EFFECT OF E-AUDIT, AI, AND BIG DATA ANALYTICS ON AUDIT QUALITY: EMPIRICAL STUDY AT BPK RI - Tabita Salsabilla; Edy Supriyono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This investigation purposes to obtain empirical evidence regarding the effects of e-audit, Artificial Intelligence (AI)-based audit technology, and Big Data Analytics (BDA) on financial audit quality at the Audit Board of the Republic of Indonesia (BPK RI). Primary data were gathered through structured questionnaires administered to BPK RI auditors, and respondents were selected via simple random sampling based on the Slovin formula with a ten-percent margin of error. Quantitative analysis was conducted utilizing IBM SPSS version 27, encompassing descriptive statistics, data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The study establishes that both e-audit and Big Data Analytics (BDA) exert a statistically positive and significant effect on audit quality. In contrast, AI-based audit technology did not demonstrate a statistically positive and significant effect on audit quality. Keywords : e-Audit, Artificial Intelligence (AI)-Based Audit Technology, Big Data Analytics, Audit Quality